Validation of Simultaneous Quantitative Method of HIV Protease Inhibitors Atazanavir, Darunavir and Ritonavir in Human Plasma by UPLC-MS/MS - Tulsidas Mishra; Pranav S. Shrivastav (The Scientific World Journal)
Objectives. HIV protease inhibitors are used in the treatment of patients suffering from AIDS and they act at the final stage of viral replication by interfering with the HIV protease enzyme. The paper describes a selective, sensitive, and robust method for simultaneous determination of three protease inhibitors atazanavir, darunavir and ritonavir in human plasma by ultra performance liquid chromatography-tandem mass spectrometry. Materials and Methods. The sample pretreatment consisted of solid phase extraction of analytes and their deuterated analogs as internal standards from 50 μL human plasma. Chromatographic separation of analytes was performed on Waters Acquity UPLC C18 (50 × 2.1 mm, 1.7 μm) column under gradient conditions using 10 mM ammonium formate, pH 4.0, and acetonitrile as the mobile phase. Results. The method was established over a concentration range of 5.0–6000 ng/mL for atazanavir, 5.0–5000 ng/mL for darunavir and 1.0–500 ng/mL for ritonavir. Accuracy, precision, matrix effect, recovery, and stability of the analytes were evaluated as per US FDA guidelines. Conclusions. The efficiency of sample preparation, short analysis time, and high selectivity permit simultaneous estimation of these inhibitors. The validated method can be useful in determining plasma concentration of these protease inhibitors for therapeutic drug monitoring and in high throughput clinical studies.